2006
DOI: 10.1002/mop.21635
|View full text |Cite
|
Sign up to set email alerts
|

Planar compact, broad‐stopband elliptic‐function lowpass filters using high‐permittivity ceramic substrate

Abstract: design and also in fabrication, the resultant CP is not pure, corresponding a finite cross-polar level.The simulated and measured radiation patterns are shown in Figure 5. For the designed sample, the measured results of Ϫ26-dB cross-polar level, Ϫ13-dB side-lobe level, ϳ13.5°half-power beamwidth, and 17.3-dBi gain corresponding to ϳ40% aperture efficiency are obtained. The bandwidth for cross-polar level less than Ϫ15 dB excesses 8%. Hence, the precise polarized variability by adjusting and ␣ in a relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, further miniaturization becomes more difficult for this filter. Planar filters using high-permittivity ceramic substrate, such as parallel-coupled filter [2], interdigital filter [3], combline filters [4], and hairpin filter [5][6][7][8][9], provide good miniaturization ability. Generally speaking, a conventional half-wavelength open-line microstrip resonator is too large to be used in modern communication systems such as personal communication systems at 900 and 1800 MHz, and wireless location area networks at 2.4 and 5.3 GHz [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further miniaturization becomes more difficult for this filter. Planar filters using high-permittivity ceramic substrate, such as parallel-coupled filter [2], interdigital filter [3], combline filters [4], and hairpin filter [5][6][7][8][9], provide good miniaturization ability. Generally speaking, a conventional half-wavelength open-line microstrip resonator is too large to be used in modern communication systems such as personal communication systems at 900 and 1800 MHz, and wireless location area networks at 2.4 and 5.3 GHz [2].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that CSRR etched in the ground plane or in the conductor strip of planar transmission media (microstrip or CPW) provide a negative effective permittivity to the structure. CSRR has been successfully applied to the narrow band filters and diplexer with compact dimensions [7,8].…”
Section: Introductionmentioning
confidence: 99%